Significance of monitoring the levels of thyroid hormone antibodies and glucose and lipid metabolism antibodies in patients suffer from type 2 diabetes - Liu Xuefang; Qiu Youyan; Chen Dandan; Xiong Jingni; Xia Biwen; Chen Caiqin; Li Suyan (Open Medicine, 2023)
The association of thyroid hormone antibodies and glycolipid metabolism indicators with Type 2 diabetes mellitus (T2DM) was explored. As the disease worsens, the levels of thyroglobulin antibody (TGAb), thyroid peroxidase antibody (TPOAb), and thyroid-stimulating hormone (TSH) was increased, and the levels of total tri-iodothyronine (TT3) and total thyroxine (TT4) was decreased (P < 0.001). The severe, medium, and light group had higher level of high-density lipoprotein (HDL), lower level of total cholesterol (TC), low-density lipoprotein (LDL), glycosylated hemoglobin (HbA1c), triacylglycerol (TAG), and fasting blood sugar (FBG) than the control group (P ＜ 0.05). The level of HDL was lower in the severe group than the light group and the medium group, but the levels of TC, LDL, HbA1c, TAG, and FBG were increased with the progress of T2DM (P ＜ 0.001). The levels of TGAb, TPOAb, and TSH in patients with T2DM were positively correlated with the levels of TC, LDL, HbA1c, TAG, and FBG (P < 0.05), and were negatively correlated with HDL levels (P < 0.05). The life quality score was lower in the severe group than the light and the medium group (P < 0.001). Among the above indicators, the predictive value of TT3, TT4, and HbA1c in T2DM was better. Clinically, detecting the levels of thyroid hormone antibodies and glycolipid metabolism indicators had a certain predictive value for the severity of T2DM.